Durability of PE gas pipes : effect of squeezing - Choy, Bernard Jun Hao (2015)
Squeeze off is a method to isolate a particular segment of the gas pipelines in order to service/repair a section downstream. There are extensive studies on properties, such as compressive strength and wall thickness changes, of polyethylene pipe immediately after squeeze off. Polyethylene is viscoelastic. Wall thickness recovery is expected to occur. However, limited information is available on how mechanical properties of polyethylene pipe will change due to viscoelastic effect in order to allow multiple squeezing at specific location. This report will be addressing this issue. Experiments on the changes of wall thickness, when given time for recovery of a fixed interval of 15 days, between each squeeze off are investigated. Corresponding changes in the dynamic properties, elastic and viscous components, and compressive strength of polyethylene pipes are also investigated. Based on this study, it is concluded that polyethylene pipes should not undergo more than one squeeze off at a specific location.